A new species of subgenus Seriphidium of Artemisia L. (Asteraceae) from Turkey - Kursat, Murat; Civelek, Semsettin; Turkoglu, Ismail; Tabur, Selma; Gur, Nazmi (Tubitak Scientific & Technological Research Council Turkey, 2015)
Artemisia bashkalensis Kursat & Civelek sp. nov. from Hakkari Province in East Anatolia, Turkey, has been described. The differences between Artemisia bashkalensis and the related species Artemisia stenocephala Krash. ex Poljak. and Artemisia khorassanica Podl. are reported. The diagnosis, description, distribution map, and taxonomic comments on the new species are provided.
Keywords: Artemisia; Asteraceae; endemic; new species; Turkey